2020
DOI: 10.1038/s41598-020-72937-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete intraureteral stent placement relieves daytime urinary frequency compared with conventional placement in patients with an indwelling ureteral stent: post-hoc analysis of a randomized, controlled trial

Abstract: A previous randomized, controlled trial had demonstrated that complete intraureteral stent placement (CIU-SP) was superior to conventional stent placement (C-SP) in terms of improvement of stent-related urinary symptoms. However, it is unclear as to which subdomain symptom and cohort could benefit the most from CIU-SP compared to C-SP in urinary symptoms while considering the baseline urinary status. To determine this, a post-hoc analysis was performed using data from a previous study (CIU-SP group, n = 39; C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They found that patients with mild baseline lower urinary tract symptoms (LUTS) benefited more from intraureteral stent placement compared to those with moderate or severe baseline LUTS [16]. Additionally, patients with baseline storage symptoms, particularly daytime frequency, showed greater benefit [16]. These studies add to the literature that limiting material within the bladder reduces stent-associated symptoms and stenting across the ureteral orifice may not be necessary.…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 94%
See 2 more Smart Citations
“…They found that patients with mild baseline lower urinary tract symptoms (LUTS) benefited more from intraureteral stent placement compared to those with moderate or severe baseline LUTS [16]. Additionally, patients with baseline storage symptoms, particularly daytime frequency, showed greater benefit [16]. These studies add to the literature that limiting material within the bladder reduces stent-associated symptoms and stenting across the ureteral orifice may not be necessary.…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 94%
“…Yoshida performed a RCT that demonstrated superior outcomes in terms of stent-related symptoms of intraureteral stent placement (Polaris Loop, Boston Scientific, Marlborough, Massachusetts, USA) compared to the conventional placement of double pigtail stents [15]. A more recent investigation in 2020, by Matsuki et al , performed a posthoc analysis looking into which subset of patients may benefit from intraureteral stent placement [16]. They found that patients with mild baseline lower urinary tract symptoms (LUTS) benefited more from intraureteral stent placement compared to those with moderate or severe baseline LUTS [16].…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 99%
See 1 more Smart Citation